Functional traits of cryptogams in Mediterranean ecosystems are driven by water, light and substrate interactions. (13th September 2013) - Giordani, Paolo; Incerti, Guido; Rizzi, Guido; Rellini, Ivano; Nimis, Pier Luigi; Modenesi, Paolo; Güsewell, Sabine
Abstract Question Poikilohydric organisms can survive desiccation without damage and recover soon after re‐wetting. In this work we explore the realized niches of epilithic, poikilohydric organisms, i.e. lichenized and lichenicolous fungi and bryophytes, grouped into 15 functional guilds based on growth form, reproductive strategy and photosynthetic traits. We hypothesize that in Mediterranean ecosystems, the distribution of these guilds is controlled by water availability and solar radiation, together with characteristics of the substrate. Location Western Sardinia (Italy). The area hosts Mediterranean Quercus ilex forests on basaltic substrata within an agroforestry landscape. Methods The presence or absence of species from each guild was recorded in 1025 small quadrats (10 × 10 cm). Four environmental variables were measured: solar radiation, microtopography (potential water run‐off), substrate roughness and number of cracks. The occurrence of each guild was related to environmental variables using non‐parametric multiplicative regression, and ecological niches of the guilds were derived from those models. Results The occurrence of all functional guilds varied significantly according to the selected environmental variables. In most cases, solar radiation was the most important variable; TI was included first in the model of two sorediate guilds, whereas four sexually reproducing functional guilds had surface relief as first variable. The growth forms were separated along a gradient of increasing solar radiation, whereas water run‐off and surface roughness mainly discriminated reproductive strategies and photobionts. Vegetatively reproducing guilds with other photobionts than Euphyta‐like pigments were confined to the border of the ecological space, defined by gradients of environmental factors, which was largely occupied by more competitive, sexually reproducing organisms. Conclusions Functional traits of epilithic poikilohydric organisms were associated with ecological adaptations to the stressful environment of Mediterranean outcrops. We showed that their response in terms of probability of occurrence is coherent with quantitative gradients of solar radiation and water availability at the micro‐scale.